Perencanaan Dan Pembuatan Struktur Rangka Wahana Terbang Hexacopter - April Yando; Kaspul Anuar; Musthafa Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Hexacopter is the development of a helicopter that only has a rotor. Hexacopter has become a lot of research objects, one of them is in agriculture. This technology is feasible to be used and developed to help agriculture activities that are appropriate and efficient. One of them is to avoid direct contact with the body due to conventional use of pesticides. To minimize this risk, a special hexacopter remote control vehicle was designed to spray pesticide liquid on plants. The hexacopter used in this study is the hexacopter type X with a wheelbase dimension of 1120 mm and a diagonal of the center plate of 300 mm. Hexacopter is made using carbon fiber composite material on the arm and middle plate, acrylic material on the clamp and polyacid material on the mounting. In the process of planning and making a carbon fiber composites, it is carried out using the hand layup and vacuum bagging method. So, that the results obtained with a wheelbase length of 1114 mm and a diagonal of the middle plate of 295 mm. Keywords: Hexacopter, Composite, Hand Lay-up and Vacuum Bagging